The Effect of Return on Assets, Return on Equity, and Loan-to-Deposit Ratio on Capital Adequacy Ratio: Evidence from Indonesian State-Owned Banks - Dimas Pranoto; Atwal Arifin (Universitas Muhammadiyah Makassar, 2025)
This study aims to analyze the effect of Return on Assets (ROA), Return on Equity (ROE), and Loan-to-Deposit Ratio (LDR) on the Capital Adequacy Ratio (CAR) of state-owned banks in Indonesia. Maintaining an optimal CAR is crucial for banks to ensure financial stability and compliance with regulatory requirements. To address this objective, panel data regression analysis was employed using secondary data obtained from the annual reports of state-owned banks for the 2019–2023 period. Several diagnostic tests were conducted to select the most appropriate model, and the Random Effect Model (REM) was determined to be the best fit. The empirical findings demonstrate that ROA, ROE, and LDR jointly exert a statistically significant influence on CAR, indicating that bank profitability and liquidity collectively play a role in determining capital adequacy. However, the partial results of the t-test reveal that only ROA has a significant positive effect on CAR, while ROE and LDR show no significant effect. These results highlight the importance of profitability, as measured by ROA, in strengthening capital adequacy. The findings provide valuable insights for policymakers as a reference for designing strategies to maintain banking stability, for banking institutions as input for evaluating financial health, and for investors and potential investors as a basis for assessing bank soundness before making investment decisions.